Investigating the association of self‐image and brain maps in medical students: A quantitative electroencephalography study - Hamid Dehghan; Arvin Hedayati; Arash Mani (PCN Reports)
Abstract Aim Self‐image, conceived as one's mental blueprint and a composite of thoughts, is among the hotly debated topics in psychology. Exploring the brain's structure, functionality, and physiology has also proven crucial in understanding one's self‐image. In this vein, the current study aimed to examine the relationship between quantitative electroencephalography (QEEG) findings and medical students' self‐image. Methods To measure self‐image, the Offer Self‐Image Questionnaire and, for the QEEG findings, a Mitsar EEG‐202 device were used. To analyze the QEEG findings, the FDA‐approved Neuroguide software was utilized. Results In the first phase, out of the 93 questionnaires returned, the maximum score, on a scale of 1 to 6, was 5.52 and the minimum was 2.36. Hence, it could be argued that the medical students who took part in this study had relatively high self‐images. Results, however, showed no significant difference between the two genders regarding either their overall self‐image score or any of its subcategories. In the second phase, the QEEG analyses of high‐ and low‐self‐image students suggested a statistically significant difference in their θ signal of the frontal lobes. Further analysis indicated that the difference was not localized to any single lead or lobe, but pertained to the overall function of the prefrontal cortices. Conclusion The relationship observed between medical students' self‐image and their brain θ waves could contribute to a better understanding of people's cognitive functions.